2016
DOI: 10.20944/preprints201610.0042.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualizing Electromagnetic Vacuum by MRI

Abstract: Based upon Maxwell's equations, it has long been established that oscillating electromagnetic (EM) fields incident upon a metal surface decay exponentially inside the conductor, 1-3 leading to a virtual EM vacuum at sufficient depths. Magnetic resonance imaging (MRI) utilizes radiofrequency (r.f.) EM fields to produce images. Here we present the first visualization of a virtual EM vacuum inside a bulk metal strip by MRI, amongst several novel findings.We uncover unexpected MRI intensity patterns arising from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Chandrashekar et al investigated the Ru(III)-catalysed oxidation of nicotinamide in HCl at 303 K using bromamine-T (BAT) as the oxidant (Scheme 74). 103 Their study revealed that the rate of the reaction follows first-order kinetics in terms [BAT] and [Ru(III)], whereas, the reaction rate exhibits inverse fractional-order dependence based on [H + ] and fractional-order dependence with respect to [nicotinamide]. The dielectric constant and the addition of halide ions and p-toluenesulfonamide did not enforce any significant impact on the reaction rate.…”
Section: Scheme 73 Oxidation Of Piperazines By Bromamine-tmentioning
confidence: 97%
See 1 more Smart Citation
“…Chandrashekar et al investigated the Ru(III)-catalysed oxidation of nicotinamide in HCl at 303 K using bromamine-T (BAT) as the oxidant (Scheme 74). 103 Their study revealed that the rate of the reaction follows first-order kinetics in terms [BAT] and [Ru(III)], whereas, the reaction rate exhibits inverse fractional-order dependence based on [H + ] and fractional-order dependence with respect to [nicotinamide]. The dielectric constant and the addition of halide ions and p-toluenesulfonamide did not enforce any significant impact on the reaction rate.…”
Section: Scheme 73 Oxidation Of Piperazines By Bromamine-tmentioning
confidence: 97%
“…101 Gowda and colleagues investigated the kinetics behind the oxidation of piperazine, 1-methylpiperazine, and 1-ethylpiperazine by bromamine-T (BAT) in buffered acidic medium at 303 K (Scheme 73). 102 The reaction follows first-order kinetics in terms of [BAT] 0 and [piperazine] 0 , and inverse fractional-order kinetics with respect to [H + ]. It was observed that the addition of halide ions and the reaction product, i.e., p-toluenesulfonamide, along with variation of the ionic strength of the medium did not have any significant impact on the rate.…”
Section: Account Synlettmentioning
confidence: 99%